Successful transformation of yeast mitochondria with RPM1: an approach for in vivo studies of mitochondrial RNase P RNA structure, function and biosynthesis. - Sulo, P (1995)
Mitochondrial RNase P RNA (Rpm1r) is coded by the RPM1 gene of mitochondrial DNA in many yeasts. As an initial step to developing a genetic approach to the structure and biogenesis of yeast mitochondrial RNase P, biolistic transformation has been used to introduce wild type and altered RPM1 genes into strains containing no mitochondrial DNA. The introduced wild type gene does support RNase P activity demonstrating that pre-existing RNase P activity is not necessary for the biosynthesis of the enzyme. Mutations introduced into RPM1 in vitro result in reduced accumulation of mature tRNA and in an alteration of the processing of Rpm1r in vivo.